KORELASI ANTARA KELIMPAHAN VEGETASI MANGROVE DAN KERANG TOTOK Polymesoda erosa DENGAN FAKTOR LINGKUNGAN DI SEGARA ANAKAN, CILACAP - Mia Azizah (Universitas Nusa Bangsa, 2014)
Correlation Between Abundance of Mangrove Vegetation and Totok Clam (Polymesoda erosa) to Environmental Factors in Segara Anakan, Cilacap Segara Anakan ecosystem is one of the largest estuary in Java which has a high biodiversity. One of the biota totok clam (Polymesoda erosa ) that live in mangrove forests. These clams have high economic value. The study aimed to determine the correlation of abundance between mangrove community and totok clam (P. erosa) , because of abiotic environmental factors in Segara Anakan , Cilacap. Research using survey methods and sampling techniques. Sampling point were 11 stations and were 3 plot sampling respectively. The data analyzed using correlation analysis of BIO - ENV. The correlation value of the environmental factors and mangrove community was 0.362 , and the correlation value of the environmental factor and the abundance of P. erosa was 0.412. The correlation value of mangrove vegetation with an abundance Polymesoda erosa had a value of 0.468. Keywords: correlation, mangroves, Polymesoda erosa, Segara AnakanABSTRAK Ekosistem Segara Anakan merupakan salah satu estuaria terbesar di Pulau Jawa yang memiliki keanekaragaman hayati yang tinggi. Salah satu biota yang ada adalah kerang totok(Polymesoda erosa) yang hidup berasosiasi dalam hutan mangrove. Kerang ini memiliki nilai ekonomis yang cukup tinggi. Penelitian ini bertujuan untuk mengetahui korelasi antara kelimpahan komunitas mangrove dan kelimpahan kerang totok (P. erosa), yang disebabkan faktor lingkungan abiotik P. erosa di Segara anakan, Cilacap. Penelitian menggunakan metode survei dan teknik pengambilan sampel. Titik sampling dibuat 11 stasiun dengan tiap stasiun diambil 3 plot. Data dianalisis dengan menggunakan analisis korelasi BIO-ENV. Nilai korelasi faktor lingkungan dengan struktur komunitas mangrove sebesar 0,362, dan nilai korelasi faktor lingkungan dengan kelimpahan P. erosa sebesar 0,412. Nilai korelasi vegetasi mangrove dan kelimpahan kerang totok memiliki nilai sebesar 0,468.Kata kunci: korelasi, mangrove, Polymesoda erosa, Segara AnakanSegara Anakan ecosystem is one of the largest estuary in Java which has a high biodiversity. One of the biota totok clam(Polymesoda erosa ) that live in mangrove forests.These clams have high economic value. The study aimed to determine the correlation of abundance between mangrove community and totok clam (P. erosa) , because of abiotic environmental factors in Segara Anakan , Cilacap. Research using survey methods and sampling techniques. Sampling point were11 stations and were 3 plot sampling respectively. The data analyzed using correlation analysis of BIO - ENV. The correlation value of the environmental factors and mangrove community was 0.362 , and the correlation value of the environmental factor and the abundance of P. erosa was 0.412.The correlation value of mangrove vegetation with an abundance Polymesoda erosa had a value of 0.468. Keywords: correlation, mangroves, Polymesoda erosa, Segara Anakan